PERLINDUNGAN PENDUDUK SIPIL KETIKA KONFLIK BERSENJATA (PERBANDINGAN HUKUM HUMANITER INTERNASIONAL DAN HUKUM ISLAM) - Muhammad Algi Fahri (Universitas Sebelas Maret, 2018)
This study describe and examine the comparison of international humanitarian law and Islamic law on protection of woman in armed conflict. This study is a descriptive normative legal research. The research approach used by the author in this study is a comparative approach. The data used in this study are primary and secondary data. The legal materials used are the Geneva Conventions 1949, Additional Protocol I, Additional Protocol II, Al Quran and Al Hadith. The legal material analysis technique used in this study is library research. The legal material analysis technique used by the author is using the method of deductive thinking.The result shows the equation and difference of International Humanitarian Law and Islamic Law on the protection of civilian in armed conflict. The equations of both legal concept are civil protection, distiction principle, and humanity principle. The difference of both legal concept are the law of slavery, the regulations in international humanitarian law are codified and more detailed. While the regulations in Islamic law are not codified, global and abstract that need interpretation.Keywords: international humanitarian law, islamic law, protection of civilian in armed conflict.